MODIFIKASI ALAT PENCELUP BATIK SECARA MEKANIS PADA PROSES PEMBUATAN BATIK TULIS GUNA MENINGKATKAN KUALITAS WARNA - Farid Ma'ruf; Agus Prasetya; Mudjijana (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2015)
Batik is a coloration technique that is blocked by wax and uses in textile. At this time, batik from Indonesia has good quality and is preferred by market share in foreign very much. Development and demand for batik every year has enhanced that effect in establishment of many industries in Bantul district, especially. However, the enhancing number ofbatikindustryis currentlynot matchedbyenhancing outputthat be produced, not due tothe implementation oftechnologyin their production process. The research will apply technology in one of existing production process in whole process of making batik is stillcarried out manually. The tool is called a color dyeing tool that serves to give color for batik that has been given wax.The tool is maked to minimize time of production process, especially for coloration time without reducing quality. Furthermore, existence of the tool is expected to enhance profit. The tool has dimension, 1610 mm x 650 mm x 460 mm and made ofmaterials that areeasily obtainablein the market.Testing of batik and performance of the color-dyeing-tool that is produced by color-dyeing-tool showed that the colordyeing-tool can make coloration process more effective and more efficient. This is evidenced bytheshorterdyeingprocess(30minutes)sotheprofit that is earnedby theindustry becomes 65% greater than thosewithmanualmethod.Furthermore, color quality produced by this tool is better (smoother, stronger, and more color resistance) than using manual dyeing process.